A Memaknai Tradisi Sisingaan pada Upacara Adat Panganten Sunat di Kecamatan Cibiru Kota Bandung: Analisis Teori Ritual Victor Turner - Murtadho, Diran; Huriani, Yeni; Albustomi, Ahmad Gibson (Kongregasi Hati Kudus Yesus (RSCJ) Indonesia, 2025)
This study aims to examine the meaning and role of the Sisingaan tradition in circumcision ceremonies in Cibiru District, Bandung City, West Java, and to understand how this tradition functions as a symbol of social solidarity and cultural identity. The research method used is a qualitative approach, with data collection through interviews with cultural leaders and participants of the tradition, as well as direct observation of the Sisingaan procession. The findings reveal that Sisingaan carries profound symbolic meaning, serving as a symbol of social transition and resistance against oppression. Furthermore, this tradition plays a significant role in strengthening social bonds and preserving cultural identity amid modernization. This study contributes to enriching the understanding of the role of rituals in Sundanese society and applies Victor Turner's ritual theory to interpret the dimensions of liminality and communitas in Sisingaan. The findings also provide insights into how this tradition can adapt to a modern context without losing its cultural significance.